Species of Licea Schrad. (Myxomycetes) in Kedrovaya Pad State Nature Biosphere Reserve (Far East, Russia), including two new species - Bortnikov, Fedor M.; Gmoshinskiy, Vladimir I.; Novozhilov, Yuri K. (Phytotaxa, 2022)
Seventeen Licea species found in Kedrovaya Pad State Biosphere Nature Reserve (Russian Far East, Primorsky Krai) are described and illustrated, including rare species: L. atricapilla, L. craterioides, L. poculiformis, and L. pseudoconica, and two species new for science: L. mariae and L. synchrysospora. Descriptions of the new species are accompanied by LM and SEM microphotographs, which illustrate their main distinguishing features. Some morphological similarity between the species of the genus Licea (L. atricapilla, L. metallica and L. iridescens) with the iridescent peridium is discussed. Some comments on the differentiation between L. pusilla and L. pygmaea are made and data on the intermediate forms between these species are given.